A new species of the plume moth genus Adaina Tutt (Lepidoptera, Pterophoridae) from the Atacama Desert, Chile - Vargas, Héctor A. (Zootaxa, 2025)
The plume moth Adaina azapensis sp. nov. (Lepidoptera, Pterophoridae, Pterophorinae, Oidaematophorini) from the transverse valleys of the Atacama Desert, northern Chile, is described and illustrated based on adults reared from florivorous larvae collected on the native shrub Pluchea chingoyo (Asteraceae). The morphology and larval feeding behavior of A. azapensis sp. nov. resemble those of A. jobimi Vargas from the Andes of northern Chile. However, the two species can be distinguished based on their wing pattern and morphological details of their genitalia. A maximum likelihood analysis based on mitochondrial DNA sequences clustered A. azapensis sp. nov. and A. jobimi as sister species with a genetic distance of 7.8% (Kimura 2-parameter model) and supports their adscription to Adaina Tutt. However, the result of the analysis also suggests that the current circumscription of this genus needs further evaluation. The discovery of A. azapensis sp. nov. highlights the need to continue searching for plume moths that remain overlooked in underexplored areas of South America.